Within-Community Conflict on Mining Policy: Assessing Implication in Rural Indonesia - Laila Kholid Alfirdaus; Teguh Yuwono; Hendra Ardianto; Dzunuwwanus Ghulam Manar (Universitas Pendidikan Ganesha, 2023)
The case of Kendeng, Rembang regency, Central Java, due to the expansion of cement factory buildings in Tuban and Gresik East Java, has led to conflict not only between the community and policymakers but also between community members. This paper discusses the fragmentation in the community by mapping argumentation behind pro and contra the policy. Based on research during 2018-2019, applying desk study, interviews, and direct observation, this paper identifies that the conflict has led to the social grouping into pro-, anti-cement, and neutral people, which impacted the daily social life of the community. The grouping has created tension in daily social relationships, creating fragmentation among the village community members. The case allows us to reflect more on the need for the policy to be aware of the social impact of a development policy within the community; moreover, for rural communities, the neighborhood is a crucial institution for them.